PENANGGULANGAN GIZI BURUK MELALUI ANALISIS SIKAP DAN KEBIASAAN IBU DALAM PENGATURAN MAKANAN KELUARGA - Elida Elida; Lucy Fridayati (Food and Nutrition Society of Indonesia, 2011)
The aim of this research is to analyze mother behavior and family food management to prevent malnutrition. The population of this research was mothers of malnourished children in Kuranji District of Padang City. Asmany as 65 mothers were taken using technique of random sampling. Results show that mother behavior and family food management were categorized as good and might not be responsible to the incidence of malnutrition.